MATHEMATICAL MODELING OF ICE FLOW IN QUEEN MAUD LAND, ANTARCTICA, AND ITS APPLICATION TO THE LATE QUATERNARY CLIMATIC PALEORECONSTRUCTION - O. Rybak O.; P. Huybrechts; O. Рыбак O.; Ф. Хёбрехтс (Ice and Snow, 2015)
One of the main sources of our knowledge about past air temperature variations is the isotopic composition of the ice cores obtained during deep drilling of the ice sheets. During 2001–2006 deep drilling was carried out at Kohnen station in Dronning Maud Land, Antarcticawithin the frameworks of the European Project for Ice Coring in Antarctica (EPICA). As a result, an ice core of 2774 mlength was obtained. Variations of air temperature are linearly dependent on isotopic composition of an ice core, but the reconstructed temperature series contains besides the climatic signal, a topographic bias. Appearance of this bias is explained by the upstream advection from the elevated sites where the ice particles were originally deposited, and by the local vertical movements of the surface of the ice sheet through time. In order to calculate this non-climatic (topographic) bias in the isotopic and reconstructed air temperature record, we applied a methodology based on mathematical ice-flow modeling. In the lower part of the ice sheet ice chronology and non-climatic biases are strongly affected by unknown value of the geothermal heat flux (G). Melt water, which was found close to the bedrock suggests that that assumed G = 54.6 mWm-2 (the average value for Antarctica) was very likely underestimated in the surroundings of Kohnen. In order to estimate the range of possible values of ice age and of non-climatic bias in the lower part of the core we carried out a series of numerical experiment with G increased by 5–30%. Один из основных источников сведений о вариациях температуры воздуха в прошлом – физико-химические свойства льда в кернах, получаемых при глубоком бурении ледниковых щитов. В 2001–2006 гг. на станции Конен на Земле Королевы Мод в Антарктиде в рамках проекта EPICA (European Project for Ice Coring in Antarctica) было проведено глубокое бурение и получен ледяной керн длиной 2774 м. Вариации температуры воздуха практически линейно связаны с вариациями изотопного состава керна, однако восстановленный ряд ...